Output feedback motion control system for observation class ROVs based on a high-gain state observer: Theoretical and experimental results. (June 2015) - Fernandes, Daniel de A.; Sørensen, Asgeir J.; Pettersen, Kristin Y.; Donha, Décio C.
Abstract: This paper proposes a motion control system for observation class ROVs. It is essentially an output feedback control system composed of a MIMO PID controller, which is aided by reference feedforward, and a high-gain observer. Feedback linearisation of the plant dynamics is also performed. Four degrees-of-freedom are controlled (surge, sway, heave, and yaw). Stability and satisfactory performance are attained under suitable and smooth reference trajectories, despite the presence of unmodelled plant dynamics, plant parameter variations, measurement errors and noise, and environmental disturbances. Results from full-scale sea trials based on NTNU׳s ROV Minerva are presented and discussed.